The Challenges of Secondary School Administration During the Pandemic of Covid-19: An Overview of Rural Schools in Sabah, Malaysia - Gurumoorthy Poobalan; Junaidi Asman; Roslee Talip; Rosna Padan; Zulhairul Ramlee; Sukuneswari Kaliappan; Ruhana @ Venel Natasha Nasir; Shanmuganathan Mookan (HRMARS, 2022)
School administration is crucial to educational management because it entails the involvement, support, and cooperation of all members of an organization to achieve educational quality and objectives. Administrative efficiency is also vital to the development of an education institution. Schools in Malaysia were also impacted by the Covid-19 pandemic. The purpose of this article is to discuss the issues and challenges facing secondary school administration during the Covid-19 pandemic. A questionnaire was distributed to rural schools in the district of Beluran, Sabah, to collect data. According to the study's findings, school administrators face four primary types of challenges, including 55% unstable internet access, 15% cost of home-based learning, 20% lack of parental cooperation, and 10% difficulty managing module delivery to rural students. Additionally, the researchers suggest several strategies for overcoming the difficulties faced by school administrators. The implications of this study provide fundamental knowledge and direction for researchers and practitioners seeking to continuously improve school administration management in accordance with new standards in line with the transformation of schools between 2021-2025.